The basics of finance : an introduction to financial markets, business finance, and portfolio management - Peterson Drake, Pamela, 1954-; Fabozzi, Frank J. (Hoboken, NJ : Wiley, 2010)
'An introductory guide to the world of finance The Basics of Finance is an accessible book for those who want to gain a better understanding of this field, but lack a strong business background. It covers essential concepts, tools, methods, and strategies in finance without delving too far into theory. Written by the experienced author team of Frank Fabozzi and Pamela Peterson Drake, this reliable resource discusses everything from financial instruments and markets to portfolio management techniques, understanding and analyzing financial statements, and different types of corporate financial strategy, planning, and policy. Explores, in a basic way, topics such as cash flow analysis, asset valuation, capital budgeting, and derivatives. Provides a solid foundation in the field of finance, which you can quickly build upon. Explains concepts in various areas of finance without getting too complicated. The Basics of Finance offers essential guidance on financial markets and institutions, corporate finance, portfolio management, risk management, and much more. If you're looking to learn more about finance, this is the best place to start.'--Provided by publisher.
What is finance? -- Financial instruments, markets, and intermediaries -- The financial system's cast of characters -- Financial statements -- Business finance -- Financial strategy and financial planning -- Dividend and dividend policies -- The corporate financing decision -- Financial risk management -- The math of finance -- Financial ratio analysis -- Cash flow analysis -- Capital budgeting -- Derivatives for controlling risk -- Investment management -- The theory of portfolio selection -- Asset pricing theory -- The structure of interest rates -- Valuing common stock -- Valuing bonds.
Includes bibliographical references and index.
Print version record.
Keywords: Finance; Electronic books